2019
DOI: 10.4103/apc.apc_121_18
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cardiopulmonary function after minimally invasive surgical repair of pectus excavatum (Nuss procedure) in children

Abstract: Background: Severe pectus excavatum in children may result in cardiorespiratory functional impairment; therefore, we evaluated cardiopulmonary response to exercise before and after the Nuss procedure. Methods: Twenty-four physically active pediatric patients aged 9–18 years with severe pectus excavatum (Haller index >3.25) were included in the study. Cardiopulmonary exercise testing using treadmill and modified Bruce protocol was performed before and after the Nuss proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…A similar lack of effect on VO 2max with the pectus bar in situ was described by Borowitz et al [ 14 ] and Castellani et al [ 8 ]. In contrast, in children with severe PE, maximum exercise capacity increased after bar placement [ 29 ], while Sigalet et al [ 15 ] reported an increase in VO 2max after bar replacement. However, 3 years after surgery and bar removal, the lower exercise performance (compared to controls) had disappeared [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar lack of effect on VO 2max with the pectus bar in situ was described by Borowitz et al [ 14 ] and Castellani et al [ 8 ]. In contrast, in children with severe PE, maximum exercise capacity increased after bar placement [ 29 ], while Sigalet et al [ 15 ] reported an increase in VO 2max after bar replacement. However, 3 years after surgery and bar removal, the lower exercise performance (compared to controls) had disappeared [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings ist dieser Effekt umstritten. Während eine systematische Übersichtsarbeit aus dem Jahr 2007 keinen eindeutigen positiven Effekt auf die kardiale Funktion nachweisen konnte [17], zeigt eine neuere Untersuchung, dass sich die physiologische Einschränkung des Herzens durch die Trichterbrustkorrektur durchaus verbessern kann [18]. Allerdings sind mögliche Komplikationen nicht zu vernachlässigen [19], wie beispielsweise eine Bügeldislokation, die in bis zu 15 % der Fälle auftreten kann.…”
Section: Introductionunclassified
“…В настоящее время этиология ВДГК до конца не изучена, предполагается, что данная патология возникает из-за структурной аномалии соединительной ткани и приводит к несбалансированному разрастанию в костохондральных областях, что ведет к вогнутому виду передней грудной стенки [2].…”
Section: Introductionunclassified